'Omics'' technologies and systems biology for engineering Saccharomyces cerevisiae strains for lignocellulosic bioethanol production. Issue 6 (November 2011) - Pinel, Dominic; Gawand, Pratish; Mahadevan, Radhakrishnan; Martin, Vincent JJ
To serve as the biocatalyst of choice for a viable lignocellulosic-based bioethanol industry, Saccharomyces cerevisiae will require extensive metabolic reprogramming for enhanced capabilities, including increased tolerance to fermentation inhibitors found in lignocellulosic hydrolysates, pentose fermentation pathways and potentially expression of cellulase activity while maintaining industrial productivity levels. Engineering of these complex traits will be facilitated by an in-depth understanding of the S. cerevisiae cellular system as a whole, incorporating transcript and protein expression, metabolite and lipid profiles and the genes that influence them. Such knowledge is being generated by taking an integrated systems approach using current and emerging 'omics'' tools. These technologies have already generated understanding and novel targets for engineering of S. cerevisiae strains, and provided the data necessary for metabolic modeling in order to aid future strain development to incorporate the multitude of traits desired of a lignocellulosic biomass to bioethanol process.